2016
DOI: 10.1080/02640414.2016.1225970
|View full text |Cite
|
Sign up to set email alerts
|

Initial foot contact and related kinematics affect impact loading rate in running

Abstract: This study assessed kinematic differences between different foot strike patterns and their relationship with peak vertical instantaneous loading rate (VILR) of the ground reaction force (GRF). Fifty-two runners ran at 3.2 m · s while we recorded GRF and lower limb kinematics and determined foot strike pattern: Typical or Atypical rearfoot strike (RFS), midfoot strike (MFS) of forefoot strike (FFS). Typical RFS had longer contact times and a lower leg stiffness than Atypical RFS and MFS. Typical RFS showed a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 29 publications
4
45
1
12
Order By: Relevance
“…This finding suggests that the collision forces acting at the foot were absorbed to a greater extent by the swing leg under the FFS condition, reducing its transmission through the upper part of the musculoskeletal system. In turn, these results are in line with classical studies in the literature comparing collision forces during running [16,[19][20][21][22]29,30], or during stepping down during ongoing gait [17]. According to van Dieën et al [17], the FFS pattern allows the ankle plantar flexors of the swing leg to produce negative work that can absorb part of the collision forces.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding suggests that the collision forces acting at the foot were absorbed to a greater extent by the swing leg under the FFS condition, reducing its transmission through the upper part of the musculoskeletal system. In turn, these results are in line with classical studies in the literature comparing collision forces during running [16,[19][20][21][22]29,30], or during stepping down during ongoing gait [17]. According to van Dieën et al [17], the FFS pattern allows the ankle plantar flexors of the swing leg to produce negative work that can absorb part of the collision forces.…”
Section: Discussionsupporting
confidence: 84%
“…However, a recent study showed that when gait was initiated with the goal of clearing an obstacle longer than 30% of body height, a change from an RFS to an FFS pattern was observed in most trials [10]. Based on previous research on the effect of the foot strike pattern on collision forces during stepping down while walking [17,18] or running [16,[19][20][21][22], it was proposed that this change in foot strike pattern reflected a strategy directed at attenuating collision forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible offsets between the motion capture approaches were evaluated, in which the offset was defined as the mean difference between both outcomes. Furthermore, two relevant discrete outcome measures for running analysis were compared for the different approaches, namely maximum knee F/E angle during stance and the ankle F/E angle at heelstrike [25], [33].…”
Section: Evaluation Measuresmentioning
confidence: 99%
“…There are three types of footstrike patterns: rearfoot strike (RFS) refers to when the heel lands before the ball of the foot; forefoot strike (FFS) refers to when the ball of the foot lands before the heel; and midfoot strike (MFS) refers to when the ball and heel of the foot land at similar times [5]. It has been reported that RFS, when compared with MFS or FFS, results in a higher impact loading [6], which has been associated with many running injuries [7]. However, greater calf strain may result from a FFS pattern, which may cause Achilles tendinitis [8].…”
Section: Introductionmentioning
confidence: 99%